Accidental epidural injection of thiopental in a dog - O’Kell, Allison L. (Canadian Veterinary Medical Association, 2010)
A 3-year-old Labrador retriever was presented to the Western College of Veterinary Medicine for a tibial plateau levelling osteotomy. While performing a pre-operative epidural, thiopental was inadvertently administered into the epidural space. Treatment included epidural saline flushing and intravenous methylprednisolone sodium succinate. No neurologic deficits were detected.